Effects of Gold Nanoparticles Functionalized with Bioactive Compounds from Cornus mas Fruit on Aorta Ultrastructural and Biochemical Changes in Rats on a Hyperlipid Diet-A Preliminary Study - Remus Moldovan; Daniela-Rodica Mitrea; Adrian Florea; Irina-Camelia Chiş; Şoimiţa Suciu; Luminiţa David; Bianca Elena Moldovan; Laura Elena Mureşan; Manuela Lenghel; Rodica Ana Ungur; Răzvan Vlad Opriş; Nicoleta Decea; et al. (MDPI AG, 2022)
Cornus mas L. extract (CM) presents hypolipidemic, antioxidant and anti-inflammatory activity. Gold nanoparticles (AuNPs) are considered potent delivery systems and may be used to release pharmaceutical compounds at the level of injury. In our study, we used gold nanoparticles functionalized with bioactive compounds from Cornus mas L. (AuNPsCM) in an experimental model of a high-fat diet (HFD), and we assessed their effects on aorta wall but also in the serum, as compared to Cornus mas (CM) administration. Sprague Dawley female rats were fed for 9 months with an HFD. During the last month of the experiment, we randomly allocated the animals into three groups that received, by oral gavage: saline solution, CM solution (0.158 mg/mL polyphenols) or AuNPsCM solution (260 μg Au/kg/day), while a Control group received a standard diet and saline solution. At the end of the experiment, we performed an ultrasonography of the aorta and left ventricle and a histology and transmission electron microscopy of the aorta walls; we investigated the oxidative stress and inflammation in aorta homogenates and in serum and, in addition, the lipid profile. AuNPsCM presented better effects in comparison with the natural extract (CM) on lipid peroxidation (p < 0.01) and TNF-alpha (p < 0.001) in aorta homogenates. In serum, both CM and AuNPsCM decreased the triglycerides (p < 0.001) and C-reactive protein (CM, p < 0.01; AuNPsCM, p < 0.001) and increased the antioxidant protection (p < 0.001), in comparison with the HFD group. In intima, AuNPsCM produced ultrastructural lesions, with the disorganization of intima and subendothelial connective layer, whereas CM administration preserved the intima normal aspect, but with a thinned subendothelial connective layer. AuNPsCM oral administration presented certain antioxidant, anti-inflammatory and hypolipidemic effects in an experimental model of HFD, but with a negative impact on the ultrastructure of aorta walls, highlighted by the intima disorganization.